Inaugural Market Entry and Information Asymmetry: An Integrated Look at De Novo Entrants - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2007)
This paper examines the role of prior industry knowledge and market entry strategies on the survival hazards of de novo entrants. We rely on a census of de novo ventures in the intra-European scheduled passenger airline industry. Contrary to predictions in the existing literature, we find that targeting new markets does not confer statistically significant survivability to new entrants, unless they have prior industry knowledge. Also contrary to theoretical predictions, entrants who compete head-on with incumbents in existing markets show higher survivability because of prior industry knowledge, although the impact is smaller than those targeting new markets. Overall, there is weak evidence that survivability for new firms improve over time.